Benzoate ion determination in beverages by using a potentiometric sensor immobilized in a graphite matrix - Pezza, Leonardo [UNESP]; Santini, A. O.; Pezza, Helena Redigolo [UNESP]; Melios, C. B.; Ferreira, VJF; Nasser, ALM (Elsevier B.V., 2001)
The characteristics, performance, and application of an electrode, namely. Pt\Hg\Hg-2(Bzt)(2)\graphite, where Bzt stands for benzoate ion. are described. This electrode responds to Bzt with sensitivity of 57.7 +/- 1.0 mV/decade over the range 5 x 10(-4)-1 x 10(-1) mol l(-1) at pH 6.0-8.0 with a detection limit of 1.6 x 10(-4) mol l(-1). The electrode shows easy construction, fast response rime (between 10-30 s), low-cost, acid excellent response stability (lifetime > 6 months, in continuous use), the proposed sensor displayed good selectivity for benzoate in the presence of several carboxylate and inorganic anions. It was used to determine benzoate in various beverages by means of the standard additions method. The results obtained by using this electrode compared very favorably with those given by the official AOAC spectrophotometric method and by a HPLC procedure as well. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: benzoate sensitive electrode; potentiometry; beverages' analysis